ANALISIS GENDER TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA DOSEN DI JURUSAN AKUNTANSI POLITEKNIK NEGERI MEDAN - INDAHWATI, RINI; DELIANA, DELIANA (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011))
Based on Indahwati (2007), it can be concluded that students want lecturer to be more empathetic to them. The inability of lecturers to be empathetic to students is most likely due to the lack of job satisfaction. This research aims to present data about the level of lecturers’ job satisfaction to be analyzed by gender. The expected outcome of this research is the measurability of the level of lecturer’s job satisfaction in Accounting Department of State Polytechnic Medan and the degree of differences between male and female lecturers’ satisfaction. It could be concluded there is a significance difference between male and female lecturers’ job satisfaction.
Keywords: job satisfaction, male lecturer, female lecturer